A new steroidal glycoside from the fruits of Solanum myriacanthum. Issue 1 (22nd December 2021) - Ono, Masateru; Shimode, Mizuki; Tsutsumi, Shuhei; Yasuda, Shin; Okawa, Masafumi; Kinjo, Junei; Miyashita, Hiroyuki; Ikeda, Tsuyoshi; Yoshimitsu, Hitoshi; Nohara, Toshihiro
Abstract: A new cholestane-type steroidal glycoside, solamyriaside A (1 ), was isolated from the fruits of Solanum myriacanthum Dunal (Solanaceae), along with two known steroidal glycosides, namely, solaviaside A (2 ) and aculeatiside A (3 ), and three known steroidal alkaloid glycosides, namely, solamargine (4 ), khasianine (5 ) and solasonine (6 ), which were isolated for the first time from this plant. Based on spectroscopic data as well as chemical evidence, 1 was determined to be 3- O -α-L-rhamnopyranosyl-(1→2)- O -[α-L-rhamnopyranosyl-(1→4)]-β-D-glucopyranosyl-22 R, 25 R -cholest-5-ene-3β, 16α, 22, 26-tetraol 26- O -β-D-glucopyranoside. The cytotoxic activity of 1 –6 against HL-60 human promyelocytic leukaemia cells was examined. Compounds 4 –6 showed cytotoxic activity. Among them, 4 exhibited the strongest activity with an IC50 value of 4.64 ± 0.17 μM, similar to the activity of cisplatin, a positive control. Graphical Abstract: